2017
DOI: 10.1111/apa.13762
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis does not reduce the infection rate following percutaneous endoscopic gastrostomy in infants and children

Abstract: Percutaneous endoscopic gastrostomy was a safe procedure and antibiotic prophylaxis did not seem to decrease infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A retrospective, single-center study that comprised 129 children aged up to 18 years with a median age of 2.9 years reported peristomal infections as the most frequent complication in 10%. 18 In a report from nine tertiary centers on prospective clinical data collection from 239 children with a mean age of 6 years, percutaneous endoscopic gastrostomy tube implantation was conducted. The cumulative incidence of complications was 47.7% at 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective, single-center study that comprised 129 children aged up to 18 years with a median age of 2.9 years reported peristomal infections as the most frequent complication in 10%. 18 In a report from nine tertiary centers on prospective clinical data collection from 239 children with a mean age of 6 years, percutaneous endoscopic gastrostomy tube implantation was conducted. The cumulative incidence of complications was 47.7% at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical methods used for gastrostomy differ across various centers. 18 19 20 21 22 23 24 However, with all techniques, a foreign body is left in the wound with either stitches or T-fasteners used to anchor the stomach to the anterior abdominal wall. In addition, the infant's clinical situation, periods of cardiac insufficiency, and various phases of treatment with cytostatic drugs may influence healing.…”
Section: Discussionmentioning
confidence: 99%
“…Van Els et al 13 found that the major complication rate was 5.4% and minor complication rate was 17.8% in 129 infants and children with PEG and the most common detected peristomal infection (10%). In the same study, when compared to those who received antibiotics and those who did not receive antibiotics, they found less infection in the group that did not take antibiotics and showed that prophylactic antibiotics did not reduce infectious complications 13 . However, the use of protective antibiotics is recommended in recent guidelines 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane meta-analysis of adults (not on PD) undergoing PEG placement showed that prophylactic antibiotics decreased gastrostomy exit site infection [56]. However, in a single-center retrospective study of children, again not on PD, antibiotic prophylaxis did not decrease the risk of infectious complications [57].…”
Section: Evidence and Rationalementioning
confidence: 99%
“…Given the high dextrose content of dialysate and the potential for bacterial contamination of the peritoneum at the time of gastrostomy placement, we strongly recommend antibiotic and antifungal prophylaxis to lower the risk of peritonitis in children already on PD at the time of gastrostomy insertion. On the basis of a Cochrane review [56], ESPGHAN [5,59] recommend pre-operative antibiotic prophylaxis to reduce stomal infection rates, but do not comment on the type, timing or duration of antibiotic prophylaxis either for children on PD, or when PD and gastrostomy tubes are inserted simultaneously. ISPD [47] guidelines recommend using a single dose of cefazolin (or vancomycin if MRSA risk is high).…”
Section: Evidence and Rationalementioning
confidence: 99%